Bacillus velezensis promotes the proliferation of lactic acid bacteria and influences the fermentation quality of whole-plant corn silage - Yili Wang; Gangqing Ying; Zimo Zhang; Yu Tang; Yunhua Zhang; Lijuan Chen (Frontiers in Plant Science, 2024)
ObjectiveThis study aimed to investigate the promoting effect of a Bacillus velezensis (BV) strain on lactic acid bacteria (LAB) and determine its influence on the fermentation quality and aerobic stability of silage.MethodsFlat colony counting method was used to evaluate the effect of BV on the growth of LAB. Freshly harvested whole-plant corn was inoculated separately with BV and L. plantarum (LP), along with an uninoculated control group (CK), and assessed at 1, 3, 5, 7, 15, and 30 days of ensiling.ResultsThe results indicated that BV exhibited a proliferative effect on Weissella confusa, Lactobacillus plantarum L-2, and Pediococcus pentosaceus. And exhibited a more rapid pH reduction in BV-inoculated silage compared with that in CK and LP-inoculated silage during the initial stage of ensiling. Throughout ensiling, the BV and LP experimental groups showed enhanced silage fermentation quality over CK. Additionally, relative to LP-inoculated silage, BV-inoculated silage displayed reduced pH and propionic acid. BV also prolonged aerobic stability under aerobic conditions. The microbial community in BV-inoculated silage showed greater stability than that in LP-inoculated silage. Additionally, Firmicutes and Lactobacillus exhibited more rapid elevation initially in BV versus LP-inoculated silage, but reached comparable levels between the two inoculation groups in the later stage.ConclusionIn summary, BV enhanced the efficacy and aerobic stability of whole-plant corn silage fermentation by stimulating LAB proliferation.